Efforts for Reforming the Criminal Justice System in Implementing Rehabilitation Sentences for Drug Abusers - Utomo, Kukuh Setio; Barthos, Megawati (Al-Makki Publisher, 2024)
Drug abuse is a serious problem affecting public health and social stability in Indonesia. The criminal justice system often faces challenges in dealing with drug abuse cases, where the punitive approach often ignores the more humane aspects of rehabilitation. This study aims to evaluate the effectiveness of rehabilitation policies in the Indonesian criminal justice system related to drug abuse and identify the obstacles faced by judges in imposing rehabilitation punishment. The research method used is normative legal research, with a statutory approach to analyze various relevant laws and policies. Data was collected through literature study and document analysis. The results showed that there are several obstacles in the implementation of rehabilitation policy, including community stigma towards drug abusers, judges' lack of knowledge about the rehabilitation process, limited rehabilitation facilities, and legal uncertainty. The research also found that despite regulations supporting rehabilitation, practices in the field often favor imprisonment. To improve the effectiveness of rehabilitation policies, it is important to provide education and training to judges, develop quality rehabilitation facilities, improve inter-agency coordination, and conduct campaigns to reduce social stigma. These measures are expected to shift the paradigm of handling drug abuse from a retributive to a rehabilitative approach, supporting individual recovery and reintegration into society.